2012
DOI: 10.1590/s0100-29452012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do manejo cultural e químico na incidência e severidade da mancha-preta dos citros

Abstract: RESUMO -A citricultura apresenta vários problemas fitossanitários, dentre os quais a mancha-preta dos citros (Guignardia citricarpa). O controle desta doença baseia-se no emprego de práticas culturais e no uso de fungicidas. Avaliou-se o efeito do manejo do mato em conjunto com o químico no controle da doença. Os experimentos foram instalados em pomares de laranjeiras-doces, nos municípios de Matão, Rio Claro e Mogi Guaçu, no Estado de São Paulo. No manejo do mato, comparou-se o uso isolado de roçadeira ecológ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…In addition to chemical control, cultural control measures may be used to reduce the amount of P. citricarpa inoculum (Bellotte et al, 2009(Bellotte et al, , 2013Schutte and Kotzé, 1997), such as the removal of leaf litter with machines (Bellotte et al, 2009;Scaloppi et al, 2012;Spósito et al, 2011;Truter, 2010), the acceleration of leaf litter decomposition with urea, ammonium sulphate, sugarcane bagasse (Bellotte et al, 2009;Dewdney et al, 2018;Kotzé, 1981;van Bruggen et al, 2017), the mulching with plants that grow between rows of orchards to cover leaf litter (Bellotte et al, 2013;Schutte and Kotzé, 1997), the pruning of dead twigs Silva-Junior et al, 2016a), irrigation and balanced nutrition (Calavan, 1960;Dewdney et al, 2018;Kotzé, 1981), and the harvesting for optimal fruit quality and prevention of overlapping fruit sets (Kotzé, 1981;Spósito et al, 2008Spósito et al, , 2011. Biological control of CBS with fungi, including P. capitalensis, and bacteria have shown inhibitory effect against P. citricarpa in vitro and in vivo (Almeida, 2009;Kupper et al, 2011;Pena et al, 2017;Santos et al, 2016;Tran et al, 2019); however, there is no biocontrol agent that controls CBS with fungicide-like efficiency under field conditions.…”
Section: I S E a S E M A N Ag E M E N Tmentioning
confidence: 99%
“…In addition to chemical control, cultural control measures may be used to reduce the amount of P. citricarpa inoculum (Bellotte et al, 2009(Bellotte et al, , 2013Schutte and Kotzé, 1997), such as the removal of leaf litter with machines (Bellotte et al, 2009;Scaloppi et al, 2012;Spósito et al, 2011;Truter, 2010), the acceleration of leaf litter decomposition with urea, ammonium sulphate, sugarcane bagasse (Bellotte et al, 2009;Dewdney et al, 2018;Kotzé, 1981;van Bruggen et al, 2017), the mulching with plants that grow between rows of orchards to cover leaf litter (Bellotte et al, 2013;Schutte and Kotzé, 1997), the pruning of dead twigs Silva-Junior et al, 2016a), irrigation and balanced nutrition (Calavan, 1960;Dewdney et al, 2018;Kotzé, 1981), and the harvesting for optimal fruit quality and prevention of overlapping fruit sets (Kotzé, 1981;Spósito et al, 2008Spósito et al, , 2011. Biological control of CBS with fungi, including P. capitalensis, and bacteria have shown inhibitory effect against P. citricarpa in vitro and in vivo (Almeida, 2009;Kupper et al, 2011;Pena et al, 2017;Santos et al, 2016;Tran et al, 2019); however, there is no biocontrol agent that controls CBS with fungicide-like efficiency under field conditions.…”
Section: I S E a S E M A N Ag E M E N Tmentioning
confidence: 99%
“…The concern with treating these aspects in a preventive way becomes more economically viable, given the impact they cause when treated in a defensive way (Neves & Kalaki, 2015). In view of the above, the effective reduction of costs with the monitoring of activities encourages the use of technologies that prevent negative impacts on crops (Novaes & Santos, 2017) The values intended for preventive spraying are also aligned with the gaps identified by Scaloppi et al (2012). These authors found that, despite the direct and indirect risks related to phytosanitary aspects, the levels of control of these activities in citrus have been below the desirable ones, requiring an integrated management and the use of available techniques and technologies to measure and control production.…”
Section: Resultsmentioning
confidence: 99%
“…According to Bernardo and Bettiol (2010), psyllid is the main pest affecting the citrus crop in São Paulo State, which is one of the probable reasons why controlling this activity is almost as expensive as controlling HLB. Scaloppi et al (2012) add that the main commercial varieties of sweet orange are susceptible to the pathogen, which commercially depreciates the fruit for the fresh market. Moreover, this pathogen causes the fruit to fall before harvest, which is financially prejudicial, justifying the investment in defensive pest control.…”
Section: Resultsmentioning
confidence: 99%
“…The control of CBS is done usually by using fungicides; in Brazil, it is controlled mainly with use of cupric and strobilurin fungicides (MOTTA, 2009;VINHAS, 2011;SILVA JÚNIOR et al, 2016). Cupric fungicides are commonly applied after petal fall, corresponding to the stages F1 and F2, until the fruits reach diameter of 1 cm (STOLLER, 2010;), followed by two to five applications of strobilurin fungicides (SCALOPPI et al, 2012), covering the more susceptible period for fruits (AGUIAR et al, 2012), from petal fall until the end of the summer, when rainfall periods of more than 8 hours still occur. Ikeda (2011) reported satisfactory responses of control of CBS to the use of five or six applications of cupric fungicides combined or alternated with strobilurins.…”
Section: Introductionmentioning
confidence: 99%